Going global: foundational ideas - Gupta, Anil K. (Henry Stewart Talks, 2014)
Strategy at different levels of aggregation, Globalization of market presence, value chain, capital base, organization and mindset, The prototypical global company, Why go global?, Importance of industry economics, Globalization of Wal-Mart in different markets
Reviewed at 2017/01/31